1975
DOI: 10.1021/jo00907a005
|View full text |Cite
|
Sign up to set email alerts
|

Dye-sensitized photooxygenation of tert-butylpyrroles

Abstract: The isomeric 1,2 and 3-mono-tert-butylpyrroles were photooxygenated in methanol and acetone solvents using Rose Bengal and Methylene Blue singlet oxygen sensitizers. Their rates of photooxygenation are comparable to that of 2,5-dimethylfuran in methanol, but slower in acetone. Fifteen different photooxygenation products from both methanol and acetone solvents have been isolated, and their structures have been determined by spectroscopic methods. They include the expected 5-methoxy-and 5-hydroxylactams, 3-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
15
1
Order By: Relevance
“…We deposited Ta on pencil lead at À1.6 V to reduce Ta precursor, according to our previous report, by potentiostatic method for 30 min. It is notable that a single broad cathodic peak was observed with pencil lead unlike previous reports [34,[41][42][43].…”
Section: Electrodeposition Of Ta On Pencil Leadcontrasting
confidence: 77%
“…We deposited Ta on pencil lead at À1.6 V to reduce Ta precursor, according to our previous report, by potentiostatic method for 30 min. It is notable that a single broad cathodic peak was observed with pencil lead unlike previous reports [34,[41][42][43].…”
Section: Electrodeposition Of Ta On Pencil Leadcontrasting
confidence: 77%
“…In 1975, Lightner and Pak published a detailed investigation into the oxidation of various tert ‐butyl‐substituted pyrroles with singlet oxygen . As with previous oxidations of pyrrole with singlet oxygen, various product mixtures were observed, with pyrrolinones ( 24 and 25 ) and maleimides ( 26 ) being the major compounds obtained (Scheme ).…”
Section: Oxidation Of Pyrrole With Singlet Oxygenmentioning
confidence: 88%
“…59 Additionally, earlier studies which investigated the oxidation of substituted pyrroles with singlet oxygen suggested both C2,C3-and C2,C5-cycloadditions. [60][61][62] These studies found the product with two oxygen atoms added to the C2,C5-positions (equivalent to TP2) and the ring-opened product (equivalent to TP1). Compounds containing a maleimide, formamide, or an epoxide moiety were also identified or hypothesized as minor products.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 98%